2022
DOI: 10.1021/acs.iecr.2c01331
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Reduction by Multiple Low-Energy Electric Discharges in a Microstructured Reactor: Experiments and Modeling

Abstract: The simple, robust, and energy-efficient reduction of CO2 to useful products is a significant goal of modern chemistry and chemical engineering. In this study, a novel CO2 reduction process was introduced by employing multiple low energy non-thermal electric glow discharges at the microscale. The process is neither dependent on limited lifetime catalysts nor consumable chemicals, enabling continuous operation over long periods, and operates at atmospheric pressure and temperature, thus simplifying process impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…14 Packed towers are susceptible to plugging and have high capital and operating costs due to the packing. 15 Additionally, many researchers have reported that increasing monoethanolamine (MEA) concentrations increased overall gas side mass transfer coefficient (K Gα ). 16 Due to the high viscosity and corrosivity of MEA, high MEA concentrations are avoided in packed towers.…”
Section: Introductionmentioning
confidence: 99%
“…14 Packed towers are susceptible to plugging and have high capital and operating costs due to the packing. 15 Additionally, many researchers have reported that increasing monoethanolamine (MEA) concentrations increased overall gas side mass transfer coefficient (K Gα ). 16 Due to the high viscosity and corrosivity of MEA, high MEA concentrations are avoided in packed towers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been discovered that increasing SEI could favorably impact conversion rates but may decrease energy efficiency . Others have also sought reactor improvements such as using electrode arrays for efficiency enhancement or introducing magnetic fields into the discharge manipulation …”
Section: Introductionmentioning
confidence: 99%
“…It has been discovered that increasing SEI could favorably impact conversion rates but may decrease energy efficiency. 31 Others have also sought reactor improvements such as using electrode arrays for efficiency enhance-ment 32 or introducing magnetic fields into the discharge manipulation. 33 However, few have addressed the cost control of the plasma power supplies as well as general principles regarding the reactor design.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the microplasma at atmospheric pressure can generate a higher electron density, excited species density and electron energy while maintaining low reactant temperatures, which can be used for surface treatment without material overheat and can also selectively and with high energetic efficiency realize chemical transformations. Meanwhile, the generation of large-area microplasma at atmospheric pressure can be realized by the microelectrode arrays, which is hardly realized in large gap [8][9][10]. Therefore, microplasma at atmospheric pressure is very popular in the microsystems and portable devices, especially in the field of the medical treatment [7], surface modifications [11,12], sensing application [13,14], nanomaterials synthesis [15], CO 2 reduction [9,16], etc, because of the reduced dimensions, the absence of heat damage, a highly reactive environment and an implementable large-area discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the generation of large-area microplasma at atmospheric pressure can be realized by the microelectrode arrays, which is hardly realized in large gap [8][9][10]. Therefore, microplasma at atmospheric pressure is very popular in the microsystems and portable devices, especially in the field of the medical treatment [7], surface modifications [11,12], sensing application [13,14], nanomaterials synthesis [15], CO 2 reduction [9,16], etc, because of the reduced dimensions, the absence of heat damage, a highly reactive environment and an implementable large-area discharges.…”
Section: Introductionmentioning
confidence: 99%